2021
DOI: 10.1177/20587384211018389
|View full text |Cite
|
Sign up to set email alerts
|

Single sample scoring of hepatocellular carcinoma: A study based on data mining

Abstract: Hepatocellular carcinoma (HCC) is a high mortality malignancy and the second leading cause of cancer-related deaths. Because the immune system plays a dual role by assisting the host barrier and tumor progression, there are complex interactions with considerable prognostic significance. Herein, we performed single-sample gene set enrichment (ssGSEA) to explore the tumor microenvironment (TME) and quantify the tumor-infiltrating immune cell (TIIC) subgroups of immune responses based on the HCC cohort of The Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In addition, KEGG results indicated that the DEGs were related to the cytokine–cytokine receptor interaction pathway. Previous studies have found that this pathway always involved some immune-related genes that are involved in different cancers, such as renal cell carcinoma and hepatocellular carcinoma [ 35 , 36 ]. This pathway might be an important factor in the immunotherapy for PRAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KEGG results indicated that the DEGs were related to the cytokine–cytokine receptor interaction pathway. Previous studies have found that this pathway always involved some immune-related genes that are involved in different cancers, such as renal cell carcinoma and hepatocellular carcinoma [ 35 , 36 ]. This pathway might be an important factor in the immunotherapy for PRAD.…”
Section: Discussionmentioning
confidence: 99%
“…Another important parameter to consider is the immune response in HCC development. Zhu et al investigated immune responses based on the HCC cohort of The Cancer Genome Atlas (TCGA) database [62]. By assigning immune cell types to three different immunity groups (low, medium, and high) and following Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, the authors showed that the immunity groups differ in gene expression of ganglio series GSL producing proteins [62] (Figure 2B).…”
Section: Su Et Al Showed That Ganglioside Synthesis Is Increased In T...mentioning
confidence: 99%
“…Zhu et al investigated immune responses based on the HCC cohort of The Cancer Genome Atlas (TCGA) database [62]. By assigning immune cell types to three different immunity groups (low, medium, and high) and following Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, the authors showed that the immunity groups differ in gene expression of ganglio series GSL producing proteins [62] (Figure 2B). This poses the question as to whether the immune response (immune cell infiltration of the tumor) can be influenced and therefore immunotherapy enhanced.…”
Section: Su Et Al Showed That Ganglioside Synthesis Is Increased In T...mentioning
confidence: 99%